PERANCANGAN MEDIA PROMOSI PT. SINAR LAUT MANDIRI BERBASIS WEB - Indra Hiswara; Rahmad Fitri; Cecep Cahyadi (JRIS : Jurnal Rekayasa Informasi Swadharma, 2022)
The development of information media in the field of computerization, especially multimedia, is increasing globally, where many parties are involved either directly or indirectly in the process of delivering and receiving information. Information is provided through promotional media containing product descriptions, product prices, and company contacts. The product description contains various products, sizes, and product uses and benefits. The purpose of this study was to develop promotional media at PT. Sinar Laut Mandiri by designing a catalog with more complete product information using the Adobe Photoshop application. This promotional media is expected to make it easier for customers to see the goods that will be sold by the company. The result of this research is the creation of a Web Browser-Based Promotional Media Application Using Adobe Photoshop